Physician Experience in Technical Success of Achieving NPVR ≥ 80% of High-Intensity Focused Ultrasound Ablation for Uterine Fibroids: A Multicenter Study - Gong, Xue; Zhang, Xinyue; Liu, Dang; Yang, Chao; Zhang, Rong; Xiao, Zhibo; Chen, Wenzhi; Chen, Jinyun (Frontiers in Medical Technology, 2022)
Objective To evaluate the experience of the physician of the technical success in high-intensity focused ultrasound (HIFU) ablation of uterine fibroids with a nonperfused volume ratio (NPVR) of at least 80%. Methods Patients from a 20-center prospective study were enrolled in this study. In this study, among the 20 clinical centers, five centers had physician with >3 years of HIFU experience, and the other 15 centers initiated HIFU therapy <3 years, were defined as the experienced group and the inexperienced group, respectively. Technical success was defined as achieving NPVR ≥ 80% of uterine fibroids with no major complications and it was defined as the successful group; otherwise, it was defined as the unsuccessful group. Results A total of 1,352 patients were included at the age of 41.32 ± 5.08 years. The mean NPVR (87.48 ± 14.91%) was obtained in the inexperienced group (86.50 ± 15.76%) and in the experienced group (89.21 ± 13.12%), respectively. The multivariate analysis showed that the volume of uterus, location of fibroids, and physician experience were significantly correlated with technical success (p < 0.05). In the experienced group, 82.20% of uterine fibroids obtained NPVR ≥ 80%, compared with 75.32% in the inexperienced group, and the difference was significant (p = 0.003). The technical success rate of the experienced group was 82.00% which was higher than 75.20% of the inexperienced group (p = 0.004). Conclusion In technical success of achieving NPVR ≥ 80%, experience of the physician was positively correlated with technical success; NPVR and major complications for the inexperienced group were comparable to those of the experienced group from a clinical perspective; inexperienced physicians could reach NPVR ≥ 80% of sufficient ablation and were trustworthy in efficacy. Smaller uterus and fibroids of anterior wall were correlated with better technical success; experienced physicians still have better technical success when choosing patients with larger uterus, contributing to clinical decision-making and patient referral.